2014
DOI: 10.1007/s10103-014-1629-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evaluation of two light delivery systems for photodynamic disinfection of Candida albicans biofilm in curved root canals

Abstract: Antimicrobial photodynamic therapy (APDT) combined with endodontic treatment has been recognized as an alternative approach to complement conventional root canal disinfection methods on bacterial biofilms. We developed an in vitro model of bioluminescent Candida albicans biofilm inside curved dental root canals and investigated the microbial reduction produced when different light delivery methods are employed. Each light delivery method was evaluated in respect to the light distribution provided inside curved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…In the present study the root canals were inoculated with microorganisms for 72 hours to allow formation of the biofilm Page 13 of 28 A c c e p t e d M a n u s c r i p t 13 structure on dentin in agreement with previous research [12,13,[22][23][24][25]. These authors observed that 72h was sufficient to encourage biofilm formation and adhesion, and a sufficient time period for obtaining adequate biofilm density.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study the root canals were inoculated with microorganisms for 72 hours to allow formation of the biofilm Page 13 of 28 A c c e p t e d M a n u s c r i p t 13 structure on dentin in agreement with previous research [12,13,[22][23][24][25]. These authors observed that 72h was sufficient to encourage biofilm formation and adhesion, and a sufficient time period for obtaining adequate biofilm density.…”
Section: Discussionsupporting
confidence: 78%
“…This occurs due to structural and compositional differences existing between those microorganisms, as Gram-positive bacteria possess an outer membrane that is relatively more porous than Gramnegative bacteria, allowing greater diffusion of the photosensitizer into the cell, whereas fungi possess a cell wall, which promotes a permeability barrier with a strength in between those of Gram-positive and Gram-negative bacteria [10]. Sabino et al [25] demonstrated that PDT is an effective way to inactivate C. albicans biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Sabino et al (24) contaminated ten permanent third molar with a bioluminescent strain of C. albicans and introduced into the canals blue methylene and irradiated with laser tip either in contact with pulp chamber or within the canal using an optical diffusion fiber. Sabino et al (24) observed that both light delivery systems performed significant fungal inactivation, but when irradiation was performed with an optical diffusion fiber, microbial burden reduction was nearly 100 times more effective. Siddiqui et al (25) performed a systematic literature review and observed that 70% of the studies that fulfilled their eligibility criteria showed that PDT is more efficient in eliminating E. faecalis in infected root canals than conventional endodontic therapy and that there was an inconsistency in the methodology and laser parameters used in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we believe that for PDT clinical trials, PS should be administered after milking, as well as a conventional treatment. New light sources are constantly being developed and in of them can be coupled to an optical fiber to deliver light in a specific target, as for example in root canal decontamination [51]. Other devices with diffusing fibers have been developed to irradiate cavities such as bladder, esophagus, lung and stomach [52][53][54][55].…”
Section: Regardlessmentioning
confidence: 99%